(untitled) (Journal of Educational Sciences, 2019)
Reproductive health is the guarantor of a successful future for the country, which is why it is recommended to pay special attention to its protection and strengthening. The high incidence of early sexual intercourse, STIs, teenage pregnancies and abandonment of their own newborns, a positive attitude of adolescents to premarital sexual relations, early marriages, abortions and miscarriages, using alcohol and tobacco, lack of awareness or misinformation about sexual behavior, lack of sex education due to the high interest in the study of this problem. The article raises the actual topic of high school girls’ reproductive health. There are statistic data that indicate the reproductive health deterioration tendency. For the scientific and pedagogical study of this problem, diagnostic work was conducted among 56 female high school students with the help of a self-developed questionnaire. At this stage, the extent of their lack of awareness in this area was clarified, as well as a rather frivolous attitude to their own reproductive health and behavior. After the survey stage, we carried out educational work, including a lecture, viewing a documentary film and conducting a discussion to form more attentive attitude to their reproductive health and sexual behavior. Key words: reproductive health, adolescents, sex education.